Studying Lived Religion : Contexts and Practices. - Ammerman, Nancy Tatom (New York University Press, 2021)
"This book introduces a practice based and contextually sensitive approach to studying lived religion, employing cases from diverse disciplines, locations, and traditions and providing accessible guides to students and novice researchers eager to begin their own exploration of religious and spiritual practices"--